2022
DOI: 10.1177/16878132221082768
|View full text |Cite
|
Sign up to set email alerts
|

An overview of solid and liquid materials for adsorption-based atmospheric water harvesting

Abstract: Thermally driven adsorption-based atmospheric water harvesting (AWH) is becoming an emerging technology to provide potable water. In this regard, various adsorbent materials including solid (MOFs, silica-gels, and zeolites), liquid (CaCl2 and LiCl), and composite adsorbents are explored in the literature. This study reviews recent advancements in adsorbent materials based on their water production capacity at different conditions that is air temperature and relative humidity (RH). The MOF of type MIL-101(Cr) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 108 publications
(320 reference statements)
0
8
0
Order By: Relevance
“…The sorption-based atmospheric water harvesting is currently mostly focused on the development of new materials, but paying less attention to the entire system that should embed them thus with no clear calculation of the real energy cost [34]. Actually, complete machines based on such an approach are comparatively few and at an early stage of development [35]. Moreover, desiccant based technology very often is not employed in complete passive devices, but it only tries to minimise the energy required to obtain the vapour condensation.…”
Section: Awg Technologiesmentioning
confidence: 99%
“…The sorption-based atmospheric water harvesting is currently mostly focused on the development of new materials, but paying less attention to the entire system that should embed them thus with no clear calculation of the real energy cost [34]. Actually, complete machines based on such an approach are comparatively few and at an early stage of development [35]. Moreover, desiccant based technology very often is not employed in complete passive devices, but it only tries to minimise the energy required to obtain the vapour condensation.…”
Section: Awg Technologiesmentioning
confidence: 99%
“…Nevertheless it is not very efficient and not very adaptable to environmental conditions variations. It is mostly used whenever very small equipment is required as well as low water production (few litres/day) [20]; (iii) Desiccant substances employed to artificially enhance the water content in the treated airflow [21]. Desiccants are able to absorb a part of the vapour content of the air, even if the relative humidity is low.…”
Section: Water Extraction From Air and The Research Gap Related To Cl...mentioning
confidence: 99%
“…The process permits the extraction of water while consuming less cooling energy, but the complete balance, including the heating energy, is not favourable in comparison with the reverse cycle technique. Nevertheless, if free cooling and/or free heating can be employed, and/or natural temperature differentials can be used, the process can be effective [21]. Moreover, the technique can be interesting in cold zones where environmental air presents a dew temperature equal to or less than 4 • C, providing an alternative method to extract water that avoids defrosting cycles for the coils.…”
Section: Water Extraction From Air and The Research Gap Related To Cl...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, Ghisi et al [4,5] showed that the use of rainwater could potentially result in a 92% peak saving in potable water use. Additional potential sources of harvesting potable water from different sources include atmospheric water harvesting and other sources [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Gitte and Pendke [23] studied water conservation practices, water table fluctuations, and groundwater recharge in watershed areas.…”
Section: Introductionmentioning
confidence: 99%